PROBIOTIC CHARACTERIZATION OF THE LACTOBACILLUS ISOLATES FROM BUFFALO VAGINA - D. M. Bokhari; H. Khan; M. N. Riaz; A. W. Yunus1 (Journal of Animal and Plant Sciences, 2017)
This study was conducted to screen and select the potential probiotic bacterial strains from buffalo vagina. Five isolates were identified biochemically and at molecular level. To determine probiotic ability, tolerance to acidic conditions and bile concentration, and antibacterial activity against two indicator pathogens Salmonella typhii and Escherichia coli were tested. PCR amplification of the isolates using Lactobacillus specific primer was carried out followed by sequencing of amplified region. The results indicated that all of the isolates, belonged to different species of Lactobacillus, sharing up to 99% homology with sequences of different Lactobacillus species in the NCBI database. Three isolates were identified as Lactobacillus gasseri and one each as Lactobacillus bombicola and Lactobacillus johnsonii using specific gene sequence analysis. All of the isolates survived at pH 2 and 0.3% bile concentration and were also found to be active against S. typhii and E. coli indicating their potential use as probiotic strains.
Keywords: Acid tolerance; Bile tolerance; Buffalo vagina; Lactic acid bacteria; Lactobacillus; Probiotic